2009
DOI: 10.1136/jmg.2008.065201
|View full text |Cite
|
Sign up to set email alerts
|

Identification of loss-of-function mutations of SLC35D1 in patients with Schneckenbecken dysplasia, but not with other severe spondylodysplastic dysplasias group diseases

Abstract: Background Schneckenbecken dysplasia (SBD) is an autosomal recessive lethal skeletal dysplasia that is classified into the severe spondylodysplastic dysplasias (SSDD) group in the international nosology for skeletal dysplasias. The radiological hallmark of SBD is the snaillike configuration of the hypoplastic iliac bone. SLC35D1 (solute carrier-35D1) is a nucleotide-sugar transporter involved in proteoglycan synthesis. Recently, based on human and mouse genetic studies, we showed that loss-of-function mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 25 publications
2
35
0
Order By: Relevance
“…SD demonstrates locus heterogeneity and had previously been shown to be caused by mutations in SLC35D1 , encoding an ER-resident sugar transporter (Hiraoka et al, 2007, Furuichi et al, 2009). SD is distinguished from other severe skeletal dysplasias by the presence on radiographs of a medial projection from the ilia that resembles a snail.…”
Section: Discussionmentioning
confidence: 99%
“…SD demonstrates locus heterogeneity and had previously been shown to be caused by mutations in SLC35D1 , encoding an ER-resident sugar transporter (Hiraoka et al, 2007, Furuichi et al, 2009). SD is distinguished from other severe skeletal dysplasias by the presence on radiographs of a medial projection from the ilia that resembles a snail.…”
Section: Discussionmentioning
confidence: 99%
“…Both are caused by deficiency of enzymes involved in the metabolism of chondroitin sulfate, an essential component of cartilage matrix. We have previously shown that a functional defect of the solute carrier-35 D1 (SLC35D1) caused a severe skeletal dysplasia in mouse and human 27 28. SLC35D1 is a nucleotide sugar transporter that transports UDP-N-acetylgalactosamine and UDP-glucronic acid from the cytoplasm into the ER 29 30.…”
Section: Discussionmentioning
confidence: 99%
“…A potential candidate for ER UDP-GlcNAc transport is SLC35D1. This protein transports UDP-GlcUA, UDP-GalNAc, and UDP-GlcNAc [43,44]. SLC35D1 knockout resulted in diminished chondroitin sulfate synthesis and defective cartilage and skeletal development in mice [44].…”
Section: Glcnac Modification In the Luminal Ermentioning
confidence: 99%